2021
DOI: 10.3390/s21227670
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Realistic Sensation Using Biological Reaction Measurements for Food Videos Presented by KMMD

Abstract: We have prototyped a KANSEI multimedia display (KMMD) that is able to release scent through the screen in order to realize collaboration between images and scents. Two types of “sukiyaki” food videos were presented to subjects using this device, and a method for objectively evaluating the realistic sensation of the food videos was examined using biological reaction measurements. The sukiyaki scent was added to one type of video to improve appetite. Viewers’ saliva flow rate, line of sight, pupil diameter, auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Five studies in total utilized a wearable device during testing, however, not all employed a real-world paradigm (Gramlich et al, 2017 ; Kunihiro et al, 2017 ; Rajagoplan, 2018 ; Tomono et al, 2021 ; Yamashita et al, 2022 ). The potential of wearable fNIRS devices in in-context scenarios will be explored in greater depth in the discussion sub-chapter.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies in total utilized a wearable device during testing, however, not all employed a real-world paradigm (Gramlich et al, 2017 ; Kunihiro et al, 2017 ; Rajagoplan, 2018 ; Tomono et al, 2021 ; Yamashita et al, 2022 ). The potential of wearable fNIRS devices in in-context scenarios will be explored in greater depth in the discussion sub-chapter.…”
Section: Resultsmentioning
confidence: 99%
“…This is corroborated by the use of wearable devices in five studies, all conducted between 2017 and 2022. Devices used included the NIRSport NIRx device (Gramlich et al, 2017 ), the Pocket NIRS Duo, DynaSense, by Hamamatsu (Kunihiro et al, 2017 ), the Hb133 by Astem Co. (Yamashita et al, 2022 ), and the HOT-1000, WOT-100 by Neu Systems Inc (Rajagoplan, 2018 ; Tomono et al, 2021 ). The recent development of in-house custom systems for odor research has also shown a tendency toward low channel density, as in the case of Moein et al ( 2020 ) and Chen et al ( 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations